"Celebrity Avatar" Feasting on In-Game Items: A Gamers' Play Arena. (May 2021) - Wang, Xuhui; Butt, Asad Hassan; Zhang, Qilin; Shafique, Nouman; Ahmad, Hassan
Gamers like to socially interact with other players and show off their avatar whenever it is conceivable in performance and appearance. This study aimed to develop a new construct—"Celebrity Avatar"—based on the celebrity endorsement model and player-avatar identification theory and add value to the survey using theory of consumption value (TCV) as a mediating role. As we know, celebrity and avatar identification show a positive influence on consumer behavioral decisions, so celebrity avatars altogether as a new construct showed positive results. The self-brand connection (SBC) and fantasy have a positive effect on the celebrity avatar. We found that four components of TCV, that is, enjoyment value, character competency value, visual character value, and monetary value, are applicable for depicting how celebrity avatars can persuade consumers to buy in-game items.